Design and implementation of a direct torque control of induction machine utilizing a digital signal processor and the field programmable gate arrays - Toh, C. L.; Nik Idris, Nik Rumzi; Mohamed Yatim, Abdul Halim; Patkar, F. (2005)
Employing both DSP and FPGA in motion control will give advantages of rapid prototyping and higher switching frequency in Direct Torque Control (DTC) drive. This paper presents a high performance DTC induction motor drive with constant switching frequency and low torque and flux ripples. The experimental results prove the feasibility of the proposed controllers, which is achieved using the combination of a DSP and an FPGA.